The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.36574/jpp.v3i3.88
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Community Governance to Support Slum Upgrading in Indonesia

Abstract: Urbanism's impact creates land scarcity as a result of an imbalance in urban land between supply and demand. As a developing country, Indonesia is still striving to overcome the slum area and provide decent housing for low-income groups. In fact, the city is owned by everyone, so slum people and other low-income groups have the right to the city to enjoy the results of development and its facilities and infrastructure, including decent urban living spaces. These areas are government challenges and opportunitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
6
0
2
Order By: Relevance
“…The results of the Focus Group Discussion (FGD) illustrate that community participation has a direct relationship with socio-cultural conditions. Thus, the program for handling slum settlements, which are dominated by poor people with poor environmental conditions, will require facilitation and assistance based on community empowerment and participation by considering socio-cultural conditions towards improving environmental quality and community welfare in a sustainable manner (Surya, 2015a;Hasanawi, et al, 2019;Surya, et al, 2021b). Furthermore, the factors that influence community participation in the implementation of the slum settlement program are (i) internal factors, namely age, education level, type of work, income level and length of stay, and (ii) external factors, namely communication and leadership in this case the function and role of institutions that are less than optimal in socialization activities have an impact on the weak level of trust and community participation in program implementation.…”
Section: Source: Primary Data and Analysis Resultsmentioning
confidence: 99%
“…The results of the Focus Group Discussion (FGD) illustrate that community participation has a direct relationship with socio-cultural conditions. Thus, the program for handling slum settlements, which are dominated by poor people with poor environmental conditions, will require facilitation and assistance based on community empowerment and participation by considering socio-cultural conditions towards improving environmental quality and community welfare in a sustainable manner (Surya, 2015a;Hasanawi, et al, 2019;Surya, et al, 2021b). Furthermore, the factors that influence community participation in the implementation of the slum settlement program are (i) internal factors, namely age, education level, type of work, income level and length of stay, and (ii) external factors, namely communication and leadership in this case the function and role of institutions that are less than optimal in socialization activities have an impact on the weak level of trust and community participation in program implementation.…”
Section: Source: Primary Data and Analysis Resultsmentioning
confidence: 99%
“…This is reflective of the results in a previous study conducted by Chen et al (2019), who confirmed a stronger link between social economic status and health conditions, when compared to lifestyle and general indoor environments. Other findings identified that low economic conditions could lead to other factors, such as comorbidity, lifestyle, and unhygienic living environments, that might worsen the occupants’ health conditions [ 51 , 52 ]. Furthermore, thermal discomfort experiences exhibit a positive correlation with health problems; this signifies that respondents who struggle to sleep and experience hot indoor air exposures are predicted to be susceptible to certain health problems.…”
Section: Resultsmentioning
confidence: 99%
“…Untuk melakukan kajian terhadap strategi, diperlukan metode analisis dan proses analisis yang tepat. Cara untuk melakukan kajian terhadap strategi diperoleh dengan melakukan perbandingan antara output strategi yang tercantum dengan dokumen RP3KP dan indikator penilaian yang diambil dari beberapa literatur kunci diantaranya (Jones, 2017), (Muchadenyika & Waiswa, 2018), (Elias et al, 2017), (Danso-wiredu & Midheme, 2017), (French et al, 2019), (Hasanawi et al, 2019), dan (Muchadenyika, 2015).…”
Section: Metodologiunclassified
“…Sebagai hasil kesepakatan dalam FGD kedua direkomendasikan tipologi penanganan kumuh di masing-masing lokasi dapat dilihat pada Tabel 2. Pentingnya tata kelola berbasis masyarakat (community governance), merubah kerjasama bersifat proyek ke kerjasama berdasarkan kemanfaatan antara kedua belah pihak (Hasanawi et al, 2019). Hal ini tercermin dalam proses diskusi FGD yang cukup lama durasinya dan dengan dinamika masalah yang ditampilkan menjadi terpetakan.…”
Section: Metodologiunclassified